D&RALAB INDAGINI NON INVASIVE PER TUTTI, APPLICATE ALLA VITA DI TUTTI I GIORNI - MediaGEO, D&RALAB (Archeomatica, 2013)
FROM LEAK DETECTION TO WATER SURGES OF ELECTRICAL EQUIPMENT,CARE OF ANIMAL WELFARE DIAGNOSTICS FOR CULTURALENGAGEMENT OF D&RALAB IS AIMED AT ANYONE WHO NEEDSNON-INVASIVE DIAGNOSTIC SERVICES OR DEVELOP NEW PROTOCOLSAND APPLICATIONS IN SCIENCE.